2010
DOI: 10.1134/s000629791002001x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as source of reactive oxygen species under oxidative stress. Study with novel mitochondria-targeted antioxidants — the “Skulachev-ion” derivatives

Abstract: Production of reactive oxygen species (ROS) in mitochondria was studied using the novel mitochondria-targeted antioxidants (SkQ) in cultures of human cells. It was shown that SkQ rapidly (1-2 h) and selectively accumulated in mitochondria and prevented oxidation of mitochondrial components under oxidative stress induced by hydrogen peroxide. At nanomolar concentrations, SkQ inhibited oxidation of glutathione, fragmentation of mitochondria, and translocation of Bax from cytosol into mitochondria. The last effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
0
27
0
10
Order By: Relevance
“…The accumulation in the nucleus is likely due to the ability of this derivative of ethidium bromide to act as an intercalator. In fact, the fluorescence signal of MitoSOX increases when it interacts with DNA (16). It should also be noted that detection of ROS production using fluorescent probes is a methodologically thorny issue.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulation in the nucleus is likely due to the ability of this derivative of ethidium bromide to act as an intercalator. In fact, the fluorescence signal of MitoSOX increases when it interacts with DNA (16). It should also be noted that detection of ROS production using fluorescent probes is a methodologically thorny issue.…”
Section: Discussionmentioning
confidence: 96%
“…This finding sustains not only the feasibility and safety of further investigations but also the possibility to widen the testing to other inflammation-related pathologies. The need to refine the approach to the mitochondria-targeted therapy has also led to the development of newer drugs, such as SkQ compounds, molecules that contain a quinone antioxidant moiety that is covalently conjugated to a lipophilic cation via alkyl chains (Izyumov et al, 2010). Among these drugs, SkQ1 (plastoquinonyl-decyltriphenylphosphonium) shows the highest membrane-penetrating capacity and potent antioxidant activity (Antonenko et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The possible explanation of delayed antioxidant and protective effects of mitochondria-targeted antioxidants suggests slow redistribution of this compound in the population of mitochondria in the cell. It was shown in various cell types, including fibroblasts, that the cells contain a fraction of mitochondria with low membrane potential that would accumulate cationic antioxidants only slowly (46). These same "impaired" mitochondria probably produced the major part of ROS under oxidative stress (as observed in other cell models (48,49).…”
Section: Cell Culturementioning
confidence: 97%
“…Our earlier studies using mitochondria-targeted antioxidants demonstrated (9,44,46) that oxidative stress induced by exogenous H 2 O 2 results in an excessive production of endogenous ROS in mitochondria. That is why we have exploited this model in the following experiments.…”
Section: Cell Culturementioning
confidence: 99%